Influence of inflammatory cytokine polymorphisms on eradication rates of Helicobacter pylori - Sugimoto, Mitsushige (2009)
Pro-inflammatory cytokines and anti-inflammatory cytokines are produced in gastric mucosa from inflammatory cells activated by Helicobacter pylori (H. pylori) infection. Of the inflammatory cytokines, interleukin (IL)-1β and tumor necrosis factor (TNF)-α have a potent inhibitive effect on gastric acid production. Polymorphisms in these genes are associated with individual differences in cytokine messenger RNA levels, which result in different gastric mucosal inflammation, different acid inhibition and different gastroduodenal disease risks in response to H. pylori infection. The sustained higher intragastric pH during an eradication therapy is known to be one of the therapeutic determinants of the H. pylori eradication as well as antibiotics resistance and poor compliance. The IL-1B-511 polymorphism is related to eradication rate, and, in combined analysis of previous reports, the eradication rate in patients with the IL-1B-511 C/C genotype (77.4%, 209/270), low IL-1β producer genotype, is lower than that of the IL-1B-511 C/T and T/T genotypes (87.2%, 631/724) (Odds ratio for eradication failure: 1.98, 95% confidence interval: 1.38–2.84, P = 0.0002). Moreover, the odds ratio of combined CYP2C19 rapid metabolizer-IL-1B-511 C/C type for eradication failure is 11.15 (5.23–23.78) times that of the CYP2C19 poor metabolizer-IL-1B-511 non-C/C type. However, there is no positive data indicating the role of other inflammatory cytokine polymorphisms (e.g. IL-1RN, TNF-A or IL-10) in eradication therapy. Nevertheless, the studies show that inflammatory cytokine polymorphisms, especially the IL-1B-511 T/T genotype, are the determinants of eradication by affecting gastric acid secretion and mucosal inflammation. Therefore, the tailored eradication therapy, considering inflammatory cytokine polymorphisms, may be effective for the higher eradication rates.